2015
DOI: 10.1080/13642537.2014.996169
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the efficacy of equine-assisted interventions on psychological outcomes

Abstract: Much research attests to the beneficial effects of equine interventions on physical development and ability. However, less is known about the possible psychological benefits of horse activities, such as therapeutic riding or interactions with horses. Although there is public consensus that horses can have psychological benefits, it is an under-researched area and conclusions are largely based on anecdotal data. The little empirical evidence that is available about the efficacy of equine-assisted interventions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 38 publications
1
58
0
7
Order By: Relevance
“…AAP can be considered a specific form of AAT. Several meta‐analyses (Nimer & Lundahl, ; Souter & Miller, ) and systematic reviews (Kamioka et al, ; Kendall et al, ; Maujean, Pepping, & Kendall, ; Rossetti & King, ) have concluded that AAT is a valuable resource in the field of clinical psychology and psychiatry. More specifically, evidence from randomized controlled trials indicates that AAT has a positive effect on a wide range of psychological and social factors in patients with psychological disorders (Maujean et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…AAP can be considered a specific form of AAT. Several meta‐analyses (Nimer & Lundahl, ; Souter & Miller, ) and systematic reviews (Kamioka et al, ; Kendall et al, ; Maujean, Pepping, & Kendall, ; Rossetti & King, ) have concluded that AAT is a valuable resource in the field of clinical psychology and psychiatry. More specifically, evidence from randomized controlled trials indicates that AAT has a positive effect on a wide range of psychological and social factors in patients with psychological disorders (Maujean et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nessas buscas, não foram encontrados estudos especificamente sobre a temática. Contudo, vale ressaltar que estão disponíveis nessa base de dados uma revisão sistemática sobre a eficácia da terapia assistida por animais (Kamioka et al, 2014) e outra sobre a eficácia da equoterapia (Kendall et al, 2015), respectivamente. No entanto, nenhuma das duas abordava a questão da qualidade de vida em idosos.…”
Section: Métodounclassified
“…In particular, equine assisted therapies (EATs) are often integrated in traditional therapeutic plans for individuals with mental and physical disabilities [6][7][8]. Even though their efficacy has not been completely proved yet, some authors claim social, emotional, physical, and educational benefits for several categories of patients experiencing therapy with horses [9][10][11][12][13][14]. For instance, EAIs seem to stimulate multiple domains of functioning handling emotional, cognitive, motor, and social disabilities with or without actual riding activity [15].…”
Section: Introductionmentioning
confidence: 99%